Basic Issues Related to the Occurrence of Infections in Healthcare Facilities - Klaudia Arciszewska; Mateusz Dobosz; Michał Paprocki; Anna Mataczyńska; Aleksandra Laskowska; Aleksandra Bogoń; Aleksandra Padkowska; Jakub Maciej Pieniążek; Jakub Buczkowski (Nicolaus Copernicus University in Toruń, 2024)
Nosocomial infections means the penetration, and the development of a biological pathogenic factor in the body, which occurred in connection with the impartation of health services. These infections affect 5 to 10% of patients. Most of the hospital staff do not know or ignore the rules for reducing infections in healthcare facilities. In Poland, there is a shortage of epidemiological nurses, doctors specializing in epidemiology, bacteriology and microbiology, and statements about their position in the structure of hospital management structure. The most difficult to combat are MDRO. They are most often carried by non-disinfected hands and medical equipment, outdated ventilation and air-conditioning installations and drainage of water from healthcare facilities. In order to limit the transmission of infectious microorganisms as much as possible, health services provided in health care facilities should be properly organized. Medical personnel should be properly trained, and cleaning staff should be equipped with adequate cleaning and disinfection agents. Each medical facility should define a hospital environment monitoring program in which the rules for limiting the transmission of infectious pathogens are clearly defined. Additionally, a program should be created to encourage the selection of specializations in epidemiological and related fields for doctors and nurses in order to increase the number of personnel with such degree and direction of education.